Postoperative intraperitoneal bladder rupture detected by renal scintigraphy: The importance of postvoid imaging - Bryan Kang; Daniel Eisenberg; Nikki Sistrun; Hongju Son (World Journal of Nuclear Medicine)
Iatrogenic intraperitoneal bladder rupture is an entity that may present in a patient with idiopathic ascites. Nuclear scintigraphy is an unusual modality for the diagnosis of this etiology, and in particular, the postvoid imaging demonstrates critical findings. We present a case report, pertinent imaging, and a review of literature.